2019
DOI: 10.1051/e3sconf/20199204007
|View full text |Cite
|
Sign up to set email alerts
|

Maximum shear modulus of calcareous sand in Dejebel Dahar, Tunisia and its dependency on applied stress

Abstract: The present experimental investigation aims at investigating the small strain stiffness of calcareous sand as a function of applied stress. The calcareous sand was sampled at Tunisia's Dejebel Dahar region, and the shear wave velocity (Vs) of calcareous sand was measured using modified oedometer cell equipped with bender elements. The results of this study demonstrate that the Vs of the tested calcareous sand is smaller than that of silica sand with minimal crushable particles at relatively low applied stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…There exist discrepancies in the threshold strain reported in the past studies below which no change in stiffness has been observed and above which it responds nonlinearly. The threshold strain reported by different researchers is < 10 -3 [101,102], 10 -1 to 10 -2 [103] and 10 -6 [104]. The response analysis of a layered soil system is directly or indirectly dependent on G max , density, excitation frequency, confining pressure, thickness of layer, etc.…”
Section: Small Strain Shear Modulus Of Silt-rich Fly Ash From Bender Element Testmentioning
confidence: 99%
“…There exist discrepancies in the threshold strain reported in the past studies below which no change in stiffness has been observed and above which it responds nonlinearly. The threshold strain reported by different researchers is < 10 -3 [101,102], 10 -1 to 10 -2 [103] and 10 -6 [104]. The response analysis of a layered soil system is directly or indirectly dependent on G max , density, excitation frequency, confining pressure, thickness of layer, etc.…”
Section: Small Strain Shear Modulus Of Silt-rich Fly Ash From Bender Element Testmentioning
confidence: 99%